2021
DOI: 10.1128/mra.00977-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacillus badius NBPM-293, a Plant Growth-Promoting Strain Isolated from Rhizosphere Soil

Abstract: Bacillus species have a long history of widespread use in biocontrol and crop growth-promoting fields. Here, we present the genome sequence of the rhizobacterium B. badius NBPM-293. The genome sequence will provide valuable information for a better understanding of the mechanism of plant growth promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A good example of Bacillus spp. as a bioagent was described by Zhu et al (2021). The group found that B. velezensis either directly or indirectly defends the plant against rice blast by generating antibiotics against plant pathogenic bacteria and triggering a rice PAMPtriggered immune (PTI) response.…”
Section: Resultsmentioning
confidence: 99%
“…A good example of Bacillus spp. as a bioagent was described by Zhu et al (2021). The group found that B. velezensis either directly or indirectly defends the plant against rice blast by generating antibiotics against plant pathogenic bacteria and triggering a rice PAMPtriggered immune (PTI) response.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus species have a long history in biocontrol and crop growth-promoting applications [ 55 ]. Bacillus thuringiensis (Bt) is the most commercially successful biopesticide on the market [ 29 , 56 ].…”
Section: Rhizosphere As a Potential Reservoir Of Biopesticidesmentioning
confidence: 99%
“…Applications of Bacillus species for biocontrol and agricultural growth promotion have a long history [45]. The most commercially effective biopesticide available is Bacillus thuringiensis (Bt) [46].…”
Section: Bacteria Biocontrolmentioning
confidence: 99%